2019
DOI: 10.1364/optica.6.000147
|View full text |Cite
|
Sign up to set email alerts
|

Background-free broadband absorption spectroscopy based on interferometric suppression with a sign-inverted waveform

Abstract: Background-free methods have potentially superior detection sensitivity because of their ability to take advantage of the full laser power; they are therefore attractive to spectroscopists. We implement background-free Fourier transform spectroscopy based on coherent suppression of the background using an interferometer, whereby the central peak of the interferogram is suppressed without losing molecular absorption signatures. This results in the appearance of peaks rather than dips in the measured spectrum. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…However, the magnitude of the free induction decay signal is still related to the intensity of the excitation pulse [23] and therefore must be accounted for in a quantitative fit to extract gas properties. As a notable exception, Tomberg et al [25] demonstrated a quantitative, baseline-free technique for broadband absorption spectroscopy by interferometrically canceling the portion of the signal that depends on the source intensity in the time-domain. In this technique, light from the spectrometer that has passed through a gas sample is interfered with light from a reference channel that has been sign-inverted in a Michelson interferometer [26][27][28][29][30].…”
Section: Existing Methods For Baseline Normalizationmentioning
confidence: 99%
“…However, the magnitude of the free induction decay signal is still related to the intensity of the excitation pulse [23] and therefore must be accounted for in a quantitative fit to extract gas properties. As a notable exception, Tomberg et al [25] demonstrated a quantitative, baseline-free technique for broadband absorption spectroscopy by interferometrically canceling the portion of the signal that depends on the source intensity in the time-domain. In this technique, light from the spectrometer that has passed through a gas sample is interfered with light from a reference channel that has been sign-inverted in a Michelson interferometer [26][27][28][29][30].…”
Section: Existing Methods For Baseline Normalizationmentioning
confidence: 99%
“…We find that RMSE is proportional to (compression rate) 0.93 by least squares fitting. To show the compression capability of C-DCS for denser molecular lines, we demonstrate massively parallel spectroscopy of 10 trace gas species, which resembles to the previously reported experiment [18]. We assume a 76-m-long multi-pass gas cell filled with nitrous oxide ( and a buffer gas.…”
Section: Fig1 a Conceptual Illustration Of Compressive Dual-comb Spec...mentioning
confidence: 79%
“…It can be implemented either by a hardware instrumentation or a post numerical processing. For the hardware instrumentation, a Michelson-type interferometer is added so as to make the 𝜋 phase difference between the pulses from the two arms due to the reflection of the beam splitter, realizing the background subtraction due to the destructive interference on the detector [18]. On the other hand, for the post numerical processing of background subtraction, a reference background interferogram can be obtained either by an additional measurement [19] or a numerical baseline reconstruction [4].…”
Section: Fig1 a Conceptual Illustration Of Compressive Dual-comb Spec...mentioning
confidence: 99%
“…The strongest line of the Q Q(4 4,1 ) transition is measured with |ΔA| = 0.25 (|Δϕ| = 0.12 rad). The 1-σ sensitivity 37,39 of ΔA is 1.31×10 −4 , and the 1-σ sensitivity of Δϕ is 0.60×10 − 4 rad. Figure 4c and 4d show the series lines of the Q Q(K a =4) subbranch in the υ 1 +υ 3 band.…”
Section: Resultsmentioning
confidence: 98%